1992
DOI: 10.1136/pgmj.68.799.363
|View full text |Cite
|
Sign up to set email alerts
|

Blastomycosis-like pyoderma in a case of chronic myeloid leukaemia

Abstract: Summary:Blastomycosis-like pyoderma, a rare skin lesion which may clinically resemble true blastomycosis, is seen in immuno-compromised individuals. We report one such case in chronic myeloid leukaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…7 Among other things, it has since been deemed a form of pemphigus, a variant of dermatitis herpetiformis and a reaction to infection. 8 It has been associated not only with IBD but also with diffuse T-cell lymphoma, 9 chronic myeloid leukemia, 10 and malnutrition. 11 13 All 3 reviews discuss distinctive clinical, histopathological, and immunofluorescent findings.…”
Section: Discussionmentioning
confidence: 99%
“…7 Among other things, it has since been deemed a form of pemphigus, a variant of dermatitis herpetiformis and a reaction to infection. 8 It has been associated not only with IBD but also with diffuse T-cell lymphoma, 9 chronic myeloid leukemia, 10 and malnutrition. 11 13 All 3 reviews discuss distinctive clinical, histopathological, and immunofluorescent findings.…”
Section: Discussionmentioning
confidence: 99%
“…2 Bacteria such as Staphylococcus, 3,4 Streptococcus, 5,6 and Pseudomonas aeruginosa 7,8 have been detected in cultures of BLP samples, and cases of BLP usually respond to antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…2,6,9 Pyoderma vegetans has been associated with ulcerative colitis, 5 diffuse T-cell lymphoma, 6 alcoholism with malnutrition, 1 HIV infection, 7 and chronic myeloid leukemia. 10 Su et al 2 reported seven patients with clinically characteristic pyoderma vegetans. It was proposed that these patients had various immunocompromising conditions that predisposed them to bacterial infections, including chronic granulocytic leukemia, pulmonary granuloma, seminoma treated with x-ray irradiation, and arthritis treated with azathioprine and prednisone.…”
Section: Discussionmentioning
confidence: 98%